Testing Club Convergence in Female Smoking Prevalence - Ferretti, Fabrizio; Mariani, Michele; Sarti, Elena (Frontiers in Global Women's Health, 2022)
In this paper, we applied the concept of convergence to examine the evolution of smoking prevalence among women in 191 countries worldwide during the period 1990–2019. First, the nonlinear time-varying factor model proposed by Phillips and Sul was adopted to identify potential clusters (clubs), wherein groups of countries converge to similar female smoking rates. Second, an ordered logit regression model was used to assess the impact of cigarettes affordability on the probability of countries to fall within a given cluster. The hypothesis of global convergence was rejected. However, the clustering algorithm successfully identified five and nine clubs, within countries with increasing and decreasing smoking prevalence, respectively. Finally, a higher relative income-price (a lower cigarette affordability) increased the likelihood of belonging to a club of countries with a low prevalence of female tobacco smoking.